Cloud-based accounting challenges and integration amongst accounting and finance professionals in Nigeria - Ugbah, Andrew; Ighosewe, Felix Enaibre; Erhijakpor, Andrew, E.O. (Edelweiss Applied Science and Technology, 2025)
Although the emergence of cloud accounting (CA) has gained high momentum considering the enormous benefits it presents in all walks of human life, its integration into the financial operations and decision-making processes of firms in Nigeria remains limited due to various challenges. Consequently, this research is motivated to investigate the extent to which challenges related to security issues (SI), compatibility issues (CS), internet reliability issues (IR), subscription costs (SS), training costs (TC), and regulatory ambiguities (RA) affect CA integration in Nigeria. In light of this, questionnaires were administered to accounting and finance professionals in Asaba, Agbor, Abraka, and Ozoro in Nigeria. Data were analyzed using Partial Least Squares (PLS) with the aid of SmartPLS. Out of the 400 questionnaires distributed, 356 were retrieved and used for the analysis with the aid of SmartPLS. Prior to conducting the PLS analysis, the Kaiser-Meyer-Olkin (KMO) and Bartlett’s test of sphericity (BTS) were conducted. Overall, both KMO and BTS are used to test the suitability of the factor analysis. SPSS was used to conduct both preliminary tests. The PLS estimate reported that security issues (SI), compatibility issues (CS), internet reliability (IR), and regulatory ambiguities (RA) significantly deter CA integration. However, a moderate increase in both subscription costs (SS) and training costs (TC) increases CA integration. Therefore, the study concludes that high security issues (SI), compatibility issues (CS), internet reliability (IR), and regulatory ambiguities (RA) significantly deter CA integration, but a moderate rise in subscription costs (SS) and training costs (TC) increases CA integration. To address the security issues, the study suggests that Nigerian businesses need to conduct regular security audits and that accounting and finance professionals need to collaborate with credible CA service providers. Lastly, accountants and finance analysts need to invest in multiple computer hardware such as switches, routers, and other network gadgets.